Perancangan Aplikasi Bimbingan Skripsi Berbasis Mobile dengan menggunakan Pendekatan Design Sprint (Studi Kasus Bimbingan Skripsi Fakultas Ilmu Komputer Universitas Brawijaya) - Aji Prasetyo; Hanifah Muslimah Az-Zahra; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Students can complete college if they have completed thesis research and have met graduation requirements. For fluency in working on a thesis, students must report achievements and problems experienced while working on the thesis. Students often get problems during thesis guidance, it is difficult to meet lecturers, it is difficult to report on work results and there is no routine guidance schedule. Lecturers find it difficult to determine guidance schedules, too many students are guided, it is difficult to monitor student thesis and incomplete guidance documentation. Based on the existing problems, a prototype design of guidance application was made with Design Sprint. Sprint design can accept user input and validate early, align all team members, set clear goals, develop hypotheses and test them quickly. The design results are in the form of a mobile-based thesis guidance prototype, then in the usability study stage by giving assignments to lecturers and students not to get into trouble just need time to get used to using it. With satisfying results the writing suggests to develop results from prototypes into applications that are ready for use by lecturers and students.